Anggaran Modal Investasi Untuk Penggantian Aktiva Tetap pada PT Surya Utama Jaya Abadi di Kota Kupang - Alya Dewi Anazuhri; Lustry Rahayu; Emilia Gie; Junita Cestillia Nenabu (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the investment feasibility of replacing fixed assets at PT. Surya Utama Jaya Abadi using a capital budgeting approach. The research object focuses on the procurement of one unit of CAT 320GC excavator. The analysis methods applied are Payback Period (PP), Net Present Value (NPV), and Internal Rate of Return (IRR). The results show that the investment project is financially feasible, with a payback period of 5.5 years (shorter than the company’s 10-year maximum), a positive NPV of IDR 359,823,193.90, and an IRR of 14.6%, exceeding the company’s minimum required rate of return of 10%. These findings highlight the importance of structured capital budgeting practices to support the sustainability and growth of heavy equipment service companies.